An exploration of mathematical concepts embedded in Xhosa beadwork artifacts through an invention programme for Grade 9 learners - Myemane, Dumakazi Margaret (Rhodes University, Faculty of Education, Department of Education, 2008)
Mathematics has become increasingly important, as it is a pre-requisite for careers like architecture, science, engineering and medicine. Therefore it becomes imperative for the learners to understand and love it. In other words a sound foundation of mathematical skills and knowledge in the early stages is required. Often we hear learners asking questions like "when and where are we going to use these symbols x and y in our lives? " These questions might indicate that learners cannot link mathematics with daily life occurrences or even their own background experiences. This study is an exploration through hands-on activities of mathematical concepts embedded in beadwork artifacts. Learners' background experiences on bead work artifacts are acknowledged and explored for mathematical understanding. It is a case study, consisting of 44 learners in Grade 9 in two schools in Grahamstown. An interpretive approach is used. In order for the learners to be able to explore beadwork artifacts, they visited the Albany Museum (AM) and Msithandane Women's Project (MWP) in the community. Learners gathered information from these two sources. Beadwork artifacts in this study were used as a mediation and integration tool between culture and mathematics. Beadwork artifacts are found in the learners' cultures serving different purposes. In this study the focus was on Xhosa bead work artifacts. The hands-on activities posed challenges to learners because of their different background experiences. Some were able to draw designs but were unable to thread what they designed, whereas others were able to thread beads but were unable to draw designs. In this study learners had to use both completed bead work artifacts and drawn up designs for the investigation of mathematical concepts. Learners were able to identify symmetries in dress and in South African flag designs. Number patterns discovered were linked to their prior number pattern knowledge. The economic value of beadwork artifacts linked mathematics to the economics learning area. This study ties up with the new curriculum (C2005) and RNCS, which advocate the inclusion and integration of learning areas. In this instance, art and culture were used in mathematical activities. The study also encouraged the inclusion of participants' cultural background as a starting point for motivating them towards utilizing mathematical resources existing in their real life situations. The purpose was to make them aware that mathematics is found everywhere around us.
Keywords: Mathematics -- Study and teaching -- Psychological aspects; Mathematics -- Study and teaching -- Social aspects -- South Africa; Mathematics -- Study and teaching (Secondary) -- South Africa; Xhosa (African people); Ethnomathematics; Beadwork -- South Africa -- Eastern Cape; Beadwork, Xhosa